Rigidifying Nonplanar Perylene Diimides by Ring Fusion Toward Geometry‐Tunable Acceptors for High‐Performance Fullerene‐Free Solar Cells. Issue 5 (7th December 2015) - Zhong, Hongliang; Wu, Chen‐Hao; Li, Chang‐Zhi; Carpenter, Joshua; Chueh, Chu‐Chen; Chen, Jung‐Yao; Ade, Harald; Jen, Alex K.‐Y.
Abstract : Rigid fused perylene diimide (PDI) dimers bridged with heterocycles exhibit superior photovoltaic performance compared to their unfused semiflexible analogues. Changing the chalcogen atoms in the aromatic bridges gradually increases the twist angles between the two PDI planes, leading to a varied morphology in which the one bridged by thiophene achieves a balance and shows the best efficiency of 6.72%.